Re-imagining education rights: Inclusive framework for neurodivergent learners in South Africa - Maitumeleng A. Nthontho; Shantha Naidoo (South African Journal of Childhood Education)
Background: Neurodiversity encompasses variations in brain function and development, influencing how individuals experience and interact with the world. While neurotypical individuals follow conventional neurological patterns, neurodivergent learners require tailored educational approaches. This study examines the right to education for neurodivergent learners in South Africa, proposing an inclusive framework to meet their specific needs.